Manajemen Strategi Program Matrikulasi Dalam Meningkatkan Kompetensi Peserta Didik di MTs Zainul Hasan Genggong Probolinggo - Naqsyabandiyah, Tharikah; Izzah, Ismatul; Yunita, Arifia Retna (El-Idare, 2024)
Strategy management is an approach or process used by organizations to plan, implement, and evaluate strategic steps in achieving the objectives that have been carried out. The matriculation program is a Study Program that provides initial debriefing for new students before active learning. The competence of new learners is the ability that students must have or achieve after participating in learning. The abilities possessed by these students are a combination of knowledge, skills, values and attitudes that are reflected in the habit of thinking and acting. The research used a qualitative approach descriptive method. This study examines the implementation of the matriculation program. Implementation contains the meaning of planning, implementation and supervision. The purpose of the study was to find out 1) Implementation of Matriculation Program Strategy Management at MTs Zainul Hasan Genggong, 2) Matriculation Program Process at MTs Zainul Hasan Genggong, 3) Matriculation Program Evaluation at MTs Zainul Hasan Genggong. The results showed that MTs Zainul Hasan Genggong has successfully implemented the Matriculation program, amtsilaty method and yanbu'a method using well-structured strategy management.